AD-DÃDAH WATS-TSUâBÃN (CACING DAN ULAR) KARYAALI AHMAD BAKATSIR: ANALISIS STRUKTURAL MODEL BADR - Sangidu, Sangidu (Kajian Linguistik dan Sastra, 2008)
Ad-DÃ»dah wats-TsuâbÃ¢n âworm and snakeâ is an arabic play which represents the condition of Egypt society in conquering French imperialism. So the ideas of arrousing this play is due to the confusion, disruption, and internal and vertical conflicts within Egyptians. They made such a reaction because they couldnât find a leader who could help and protect them. Therefore, the appearance of Sulaiman Al-Jausaqi was thought as a figure who can calm them down. He was a religious man who concerned much on the problems of the society. This kind of hero was the one who successively made a strategy to fight against the French imperialism to the end of his dead as Syahid. Besides, a more alive scene and coherence of this play can be seen as in another heroic character from France, Napoleon Bonaparte.Â Key words: konflik internal dan vertikal, imperialisme, syahid, dan koherenitas.Â